Chemical and biological activity studies of fruit of Cucumis melo L. - Biswas, Tirthankar; Samiha, Zeba; Shoeb, Mohammad; Hasan, Md. Kamrul (Institut Teknologi Bandung, 2025)
Cucumis melo L. from the family Cucurbitaceae is native to Southeast Asian countries, and very well-liked fruit due to its ginormous medicinal and nutritive value. The DCM extract of the powdered fruit sample of C. melo L. was subjected to different chromatographic techniques to isolate secondary metabolites. a-spinasterol, a-spinesteryl acetate, trilinolein and oleic acid were isolated and their structures were elucidated by comparing the data obtained from 1H NMR (400 MHz) and 13C NMR (100 MHz) spectra with reported data for corresponding compounds. The total phenolic content, total flavonoid content, total antioxidant capacity and DPPH radical scavenging activity were found to be the highest for methanolic extracts (14.25 ± 0.83 mg GAE/g, 9.2 ± 0.58 mg QE/g, 33.77 ± 1.58 mg AAE/g of dry extractives, and IC50 value of 11.13 µg/mL respectively) compared to n-hexane and DCM extracts.